Influence of discharge regime on the movement and refuge use of a freshwater fish in a drying temperate region. Issue 1 (28th September 2020) - Storer, Timothy; Bannister, Jo; Bennett, Katherine; Byrnes, Evan; Crook, David A.; Morgan, David L.; Gleiss, Adrian; Beatty, Stephen J.
Abstract: Understanding how the movement and habitat use of fishes are influenced by flow regimes is important in sustainably managing river ecosystems, particularly in regions undergoing drying due to climate change. Here, we aimed to determine how the movement of a freshwater fish from refuge pools is influenced by discharge and environmental variables in south‐western Australia, a region that has suffered an ~50% reduction in surface flows since the 1970s. We quantified the movement patterns of the freshwater plotosid Tandanus bostocki using acoustic telemetry in two rivers that had different flow regimes and habitat characteristics. We hypothesized that its movements would be positively influenced by discharge and it would also display a high degree of site fidelity. Fifty fish were tagged and monitored across both rivers for a 1‐year period. There was an overall significant positive relationship between daily movements from the monitored refuge pools with both discharge and solar irradiation in both rivers. However, there was a greater probability of movement at a lower magnitude of discharge in the regulated Harvey River, which was attributed to the influence of river gradient and prevalence of instream barriers moderating the effect of flow on movements in the Brunswick River. The species demonstrated a considerable degree of site fidelity and also displayed homing behaviour. The study suggests that the maintenance of key refuge pools during baseflow, and ensuring river connectivity during the key movement periods, would help maintain the viability of the species as river discharge continues to decline due to climate change.